Erioflorin stabilizes the tumor suppressor Pdcd4 by inhibiting its interaction with the E3-ligase β-TrCP1. - Johanna S Blees; Heidi R Bokesch; Daniela Rübsamen; Kathrin Schulz; Larissa Milke; Magdalena M Bajer; Kirk R Gustafson; Curtis J Henrich; James B McMahon; Nancy H Colburn; Tobias Schmid; Bernhard Brüne (PLoS ONE)
Loss of the tumor suppressor Pdcd4 was reported for various tumor entities and proposed as a prognostic marker in tumorigenesis. We previously characterized decreased Pdcd4 protein stability in response to mitogenic stimuli, which resulted from p70(S6K1)-dependent protein phosphorylation, β-TrCP1-mediated ubiquitination, and proteasomal destruction. Following high-throughput screening of natural product extract libraries using a luciferase-based reporter assay to monitor phosphorylation-dependent proteasomal degradation of the tumor suppressor Pdcd4, we succeeded in showing that a crude extract from Eriophyllum lanatum stabilized Pdcd4 from TPA-induced degradation. Erioflorin was identified as the active component and inhibited not only degradation of the Pdcd4-luciferase-based reporter but also of endogenous Pdcd4 at low micromolar concentrations. Mechanistically, erioflorin interfered with the interaction between the E3-ubiquitin ligase β-TrCP1 and Pdcd4 in cell culture and in in vitro binding assays, consequently decreasing ubiquitination and degradation of Pdcd4. Interestingly, while erioflorin stabilized additional β-TrCP-targets (such as IκBα and β-catenin), it did not prevent the degradation of targets of other E3-ubiquitin ligases such as p21 (a Skp2-target) and HIF-1α (a pVHL-target), implying selectivity for β-TrCP. Moreover, erioflorin inhibited the tumor-associated activity of known Pdcd4- and IκBα-regulated αtranscription factors, that is, AP-1 and NF-κB, altered cell cycle progression and suppressed proliferation of various cancer cell lines. Our studies succeeded in identifying erioflorin as a novel Pdcd4 stabilizer that inhibits the interaction of Pdcd4 with the E3-ubiquitin ligase β-TrCP1. Inhibition of E3-ligase/target-protein interactions may offer the possibility to target degradation of specific proteins only as compared to general proteasome inhibition.